Young adults’ attitudes towards vaping content on Instagram: Qualitative interviews utilizing the associative imagery technique - Alpert, Jordan; Bradshaw, Amanda; Riddell, Heather; Chen, Huan; Chen, Xiaobei (Qualitative Health Communication, 2022)
Backgound: Vaping among young adults (18-24), increased 46% from 2017-2018, resulting in adverse health effects and vulnerability to nicotine dependence. Young adults spend three hours per day using social media, particularly Instagram, which is dominated by pro-vaping messages. Therefore, young adults’ exposure to vaping content can result in positive perceptions of vaping. Aim: Using the associative imagery technique, our goal was to understand the favorability of Instagram posts depicting aspects of vaping and how young adults relate to the images. Method: Semi-structured interviews were conducted with 24 young adults using the analytic induction method. Results: Three main themes emerged: 1) the power of color and visual aesthetics, meaning participants were drawn to colorful imagery; 2) distancing, when participants attempted to separate themselves from vaping culture; and 3) the environment influences perceptions, meaning participants paid attention to popular content, which enhanced its perceived credibility. Discussion: The type of social media platform and users' expectations are just as important as the vaping content. Attitudes of social vapers compared to hardcore vapers may indicate specific aspects of content perceived as appealing. Conclusions: Visually appealing vaping content impacts young adults, but they are hesitant to share content as to be labeled as a “vaper.”